D-dencichine Regulates Thrombopoiesis by Promoting Megakaryocyte Adhesion, Migration and Proplatelet Formation - Shilan Ding; Shilan Ding; Shilan Ding; Shilan Ding; Min Wang; Min Wang; Min Wang; Min Wang; Song Fang; Huibo Xu; Huiting Fan; Yu Tian; et al. (Frontiers Media S.A., 2018)
Life-threatening chemotherapy-induced thrombocytopenia can increase the risk of bleeding due to a dramatic low platelet count, which may limit or delay treatment schedules in cancer patients. The pressing need for the rapid alleviation of the symptoms of thrombocytopenia has prompted us to search for novel highly effective and safe thrombopoietic agents. Pharmacological investigations have indicated that dencichine can prevent and treat blood loss and increase the number of platelets. On the basis of the neurotoxicity of dencichine, D-dencichine is artificially synthesized in the laboratory. Our initial results showed that D-dencichine had potential to elevate peripheral platelet levels in mice with carboplatin-induced thrombocytopenia. However, the mechanisms of D-dencichine on thrombopoiesis have been poorly understood. In this study, we found that sequential administration of D-dencichine had a distinct ability to elevate numbers of reticulated platelets, and did not alter their clearance. Moreover, we demonstrated that D-dencichine was able to modulate the return of hematopoietic factors to normal levels, including thrombopoietin and IL-6. However, subsequent analysis revealed that D-dencichine treatment had no direct effects on megakaryocytes proliferation, differentiation, and polyploidization. Further in vitro studies, we demonstrated for the first time that D-dencichine significantly stimulated megakaryocyte adhesion, migration, and proplatelet formation in a dose-dependent manner through extracellular regulated protein kinases1/2 (ERK1/2) and v-akt murine thymoma viral oncogene homolog (AKT) signaling pathways. This study sufficiently characterized the role of the effects of D-dencichine treatment on the regulation of thrombopoiesis and provided a promising avenue for CIT treating.